Strategies for preventing ventilator-associated pneumonia: an integrative review - Raimunda Xavier Alecrim; Mônica Taminato; Angélica Belasco; Maria Cristina Barbosa Longo; Denise Miyuki Kusahara; Dayana Fram (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to identify studies about strategies for prevention of ventilator-associated pneumonia deployed in health services and classify their level of evidence. Method: integrative review of the literature, in 7 databases, which included the following descriptors: Prevention and Control AND Pneumonia Ventilator-Associated AND Intensive Care Units AND Bundle AND Patient Care. Results: twenty-three scientific productions were included. Of the preventive measures identified, 9 (39.1%) correspond from three to five strategies. The most frequent were: 22 (95.6%) lying with head elevated, 19 (82.6%) oral hygiene with chlorhexidine and 14 (60.8%) reduction of sedation whenever possible. Final Consideration: the application of measures based on scientific evidence is proven to be effective when carried out in conjunction, impacting the reduction of the incidence of ventilator-associated pneumonia.